2023
DOI: 10.3390/electronics12020334
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Medical Image Watermarking Scheme Based on Nature-Inspired Optimization for Telemedicine Applications

Abstract: Medical images and patient information are routinely transmitted to a remote radiologist to assist in diagnosis. It is critical in e-healthcare systems to ensure that data are accurately transmitted. Medical images of a person’s body can be used against them in many ways, including by transmitting them. Copyright and intellectual property laws prohibit the unauthorized use of medical images. Digital watermarking is used to prove the authenticity of the medical images before diagnosis. In this paper, we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The findings indicate that the envisaged system exhibited satisfactory performance, even in the presence of a filtering attack. Furthermore, upon conducting a comparative analysis of the outcomes with other extant methodologies, namely [28,[30][31][32], at intensities of 0.05, 0.025, and 0.10 (as presented in Table 5), it was noted that the findings of [31,32] bear similarity to the suggested approach at an intensity of 0.050. At the intensity of 0.025 and 0.010, the performance of our approach is much better than other similar schemes.…”
Section: Jpeg Compressionmentioning
confidence: 98%
See 4 more Smart Citations
“…The findings indicate that the envisaged system exhibited satisfactory performance, even in the presence of a filtering attack. Furthermore, upon conducting a comparative analysis of the outcomes with other extant methodologies, namely [28,[30][31][32], at intensities of 0.05, 0.025, and 0.10 (as presented in Table 5), it was noted that the findings of [31,32] bear similarity to the suggested approach at an intensity of 0.050. At the intensity of 0.025 and 0.010, the performance of our approach is much better than other similar schemes.…”
Section: Jpeg Compressionmentioning
confidence: 98%
“…The obtained results demonstrate that, when exposed to a JPEG compression attack, the proposed approach performed better than expected. Furthermore, upon conducting a comparative analysis of the outcomes with other pre-existing methodologies, namely [28,[30][31][32], concerning quality factors 80 and 90 (as presented in Table 3), it was observed that the outcomes of [28,32] exhibit a resemblance to the proposed scheme at a quality factor of 90. At a quality factor of 80, it can be observed that only the reference [32] is in closer proximity to the subject matter being discussed.…”
Section: Jpeg Compressionmentioning
confidence: 99%
See 3 more Smart Citations